2004
DOI: 10.1182/blood-2004-01-0268
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte immunoglobulin-like receptors: novel innate receptors for human basophil activation and inhibition

Abstract: Basophils, recruited from the blood to tissues, have been implicated by their presence in diverse allergic disorders including bronchial asthma, allergic rhinitis, and cutaneous contact hypersensitivity. We hypothesized that like other leukocytes involved in inflammatory responses, basophils would express members of the leukocyte immunoglobulin-like receptor (LIR) family of immunoregulatory molecules on their cell surface. We identified LIR7, an activating member coupled to the common Fc receptor gamma chain, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 68 publications
4
72
0
Order By: Relevance
“…ILT1 (LIR7) is a receptor expressed on myeloid and lymphoid cells, but that lacks ITIMs (31). It has been reported that ILT1/LIR7 activates human eosinophils and basophils (32,33). ILT7 is a similar activating receptor that has been proposed as a marker for plasmacytoid dendritic cells (34,35).…”
Section: Introductionmentioning
confidence: 97%
“…ILT1 (LIR7) is a receptor expressed on myeloid and lymphoid cells, but that lacks ITIMs (31). It has been reported that ILT1/LIR7 activates human eosinophils and basophils (32,33). ILT7 is a similar activating receptor that has been proposed as a marker for plasmacytoid dendritic cells (34,35).…”
Section: Introductionmentioning
confidence: 97%
“…29 Several lines of evidence demonstrated the role of LILRA2 in the activation of myeloid cells and macrophages. 14,[19][20][21] Thus, stronger signals via D419-421 isoform might explain its association with MPA.…”
Section: Discussionmentioning
confidence: 99%
“…LILRA2 is implicated in the activation of eosinophils, 19 basophils 20 and macrophages. 21 On the other hand, it is reported that activation of LILRA2 suppresses innate host defense mechanisms by shifting monocyte production from IL-12 toward IL-10 and blocking toll-like receptor (TLR)-mediated antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%
“…Some LILR activating receptors with short cytoplasmic tail were proved to recruit the c-chain of FceRI with charged Arg residue in transmembrane region to activate the immune system via ITAM motifs of FceRIc (75)(76)(77). Shiroishi et al demonstrated the crystal structure of LILRA5 (ILT11/LIR-9/CD85f) in 2006 and found its nonbinding with several classical and non-classical pMHCI molecules (66).…”
Section: Interaction Of Lilr (Ilt/lir/cd85) With Peptide-hlamentioning
confidence: 99%